Preservation and decay of plant remains in two Palaeolithic sites: Abrigo de la Quebrada and Cova de les Cendres (Eastern Spain). What information can be derived?. (February 2020) - Martínez-Varea, Carmen María; Carrión Marco, Yolanda; Badal, Ernestina
Highlights: The original archaeobotanical assemblage is biased by taphonomic processes. Plant remains provide information about the deposit formation. A fast burial is the first requisite for a good preservation of plant remains. Seeds and leaves are the remains most affected by post-depositional processes. Abstract: Plant remains are quickly affected by post-depositional processes once they are deposited in archaeological sites. In normal conditions, decomposing organisms cause their decay and final disappearance unless a preservation agent, as carbonisation or mineralisation, inhibit their activity. Moreover, physical and chemical processes could also lead to the partial or total destruction of the archaeobotanical assemblage. Thus, an analysis of their characteristics is useful for an assessing of the taphonomic processes. Archaeobotanical assemblages from two Palaeolithic sites, Abrigo de la Quebrada and Cova de les Cendres, have been analysed in terms of taxonomic composition of the assemblage, types of preservation and elemental composition of the remains. Both sites are compared in order to assess the different formation processes and preservation conditions of the deposits, related to the different typology of the sites (shelter vs. cave), the chronology and the human occupation pattern.